1. Efectuați:
a) (-49) : (-7):(-1) + 12 - (-2): (-6) + 14 - (-2+1);
b)(-11 - (-4) · (–19)] :(-1)+(-4). [-12 - 72 :(-4)].
Răspunsuri la întrebare
Răspuns de
7
Explicație pas cu pas:
sper sa nu fi gresit
Anexe:
Răspuns de
12
Explicație pas cu pas:
a(-49):(-7):(-1)+12-(-2):(-6)+14-(-2+1)= 7:(-7)+12-(2):(-6) +14-(-1)= -1+12-0,3+14-(-2+1)= 23,7
b.[(-11-(-4)×(-19)]: (-1)+(-4)×[-12-72:(-4)]= ( -11-76):(-1)+(-4)×(-12-18)= -87:(-5)×(-30)= -552
Alte întrebări interesante
Fizică,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă